THE EFFECT OF MIXING SODIUM HYPOCHLORITE ON COMPRESSIVE STRENGTH OF TYPE III GYPSUM PRODUCT - Rezy Kurnia; Hidayati Hidayati (Andalas Dental Journal, 2016)
Disinfection is needed to avoid transmission of infectious agents. One of disinfectant solution used is sodium hypochlorite. Disinfection should be done without changing the quality of gypsum models, so the technique of mixing a disinfectant solution on gypsum powder can be used as an alternative. The purpose of this study was to determined the effect of mixing sodium hypochlorite to the compressive strength of type III gypsum product. The study was conducted at the Laboratory of Materials and Structures, Faculty of Engineering, Andalas University using laboratory experimental method with 30 pieces of type III gypsum models as samples. Samples were divided into 5 groups, that were mixed using 0.5% sodium hypochlorite, 1% sodium hypochlorite, 2% sodium hypochlorite, 5% sodium hypochlorite and distilled water as a control group. Measurement of the compressive strength was performed with a Universal Testing Machine (UTM). The results showed that the models were mixed with 0.5% sodium hypochlorite, 1% sodium hypochlorite, 2% sodium hypochlorite and 5% sodium hypochlorite reduced the average of the compressive strength compared to the models that are mixed with distilled water. One Way ANOVA test showed that was significantly differences (p<0.05) among groups of 0.5% sodium hypochlorite, 1% sodium hypochlorite, 2% sodium hypochlorite, 5% sodium hypochlorite and distilled water as a control group. It was concluded that there were effect of mixing sodium hypochlorite to reduced the compressive strength of type III gypsum product. Keywords: type III gypsum, compressive strength, sodium hypochlorite